INDONESIA NATURAL MINERAL FOR HEAVY METAL ADSORPTION: A REVIEW - Kadja, Grandprix T. M.; Ilmi, Moh Mualliful (Journal of Environmental Science and Sustainable Development, 2019)
Indonesia has abundant mineral resources used as natural adsorbent materials for the absorption of heavy metal. Among these are natural zeolites, clay, and ashes. These natural materials showed high performance adsorption capacity with respects to their low cost and high availability. Several research reports had been published for studying the performance of the natural materials as adsorbent of several heavy metals i.e., Hg, Pb, Fe, Cd, Cr, Zn, Ni, and Cu by examining the effect of various factors, including pH, contact time, initial concentration, temperature, and dosage. Furthermore, to determine the adsorption rate, mechanism, and efficiency of natural materials in the removal of toxic metals from aqueous solution, investigations have been made of the parameters of the adsorption isotherms, kinetics, and thermodynamics. The main objective of this article is to provide an overview of the use of some natural materials found in Indonesia, including clay, natural zeolite, fly ash, and bottom ash for use as adsorbents for several types of heavy metals in aqueous solution. These types of natural adsorbents were chosen as their high availability in natural or disposal product and their high performance regarding their heavy metal uptakes. This article review is important in order to capture the current research reported the use Indonesia natural minerals as adsorbent of heavy metals and providing its future research opportunities. Thus, we also emphasize the prospect materials and the future research opportunities for the use of Indonesia's local natural minerals with the utilization of non-conventional modification techniques that can provide added value and improve the performance of these natural materials in removing heavy-metal waste from aqueous solutions.